Government Support in Zakat Management Comparative Study of Parepare City and Barru District - Arham Arham; Andi Fitriani; Muh. Alwi (Economos : Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine the support of local governments in zakat management and whether there are differences in approaches, especially in collecting zakat using a comparative study between Barru Regency and Parepare City. The data used in the study were primary data obtained through interviews or direct consultations to both the leadership and employees of BAZNAS Barru Regency and Parepare City. The research was conducted to find out how the local government actually supports zakat management and how the methods used by each region in collecting zakat. Hypothesis testing is carried out by comparing Zakat Management by BAZNAS of Barru Regency with Parepare City, based on data and facts on the ground and from the results of research can conclude that zakat management in Parepare City can be said to have not received full local government support in contrast to Barru Regency which has full support from the local government by issuing Regional Regulation Number 9 of 2017 concerning Zakat Management with several regulations and technical policies governing the obligations of Muslim ASNs in withholding zakat 2.5 percent are the main points. a better method for zakat management.